Enhanced liver fibrosis score as a surrogate of liver-related complications and mortality in primary biliary cholangitis. Issue 39 (1st October 2021) - Fujinaga, Yukihisa; Namisaki, Tadashi; Takaya, Hiroaki; Tsuji, Yuki; Suzuki, Junya; Shibamoto, Akihiko; Kubo, Takahiro; Iwai, Satoshi; Tomooka, Fumimasa; Takeda, Soichi; Fujimoto, Yuki; Enomoto, Masahide; et al.
Abstract : Abstract: The presence of bridging fibrosis predicts survival of primary biliary cholangitis (PBC). This study aimed to compare serum parameters for the estimation of liver fibrosis and prediction of clinical outcomes in PBC. Out of 392 patients with PBC, 102 who underwent liver biopsy and in whom fibrosis indices, platelet count, hyaluronic acid, type IV collagen 7 second domain, procollagen type III amino-terminal peptide, tissue inhibitor of metalloproteinases 1, Mac-2 binding protein glycosylation isomer, N-terminal type III collagen propeptide levels; fibrosis index based on 4 factors, aspartate aminotransferase-to-platelet ratio index, and enhanced liver fibrosis (ELF) score were determined, were included. The correlation of histological stages based on both Scheuer and Nakanuma classifications with fibrosis indices was investigated. The Nakanuma system comprises grading for liver fibrosis and bile duct loss. Diagnostic performances of 10 fibrosis indices were evaluated to identify patients with poor prognosis. Moreover, correlations of those with PBC clinical manifestation and survival were also investigated. Enhances liver fibrosis (ELF) score had the highest correlation coefficient for liver fibrosis evaluated according to either the Scheuer or Nakanuma classification among 10 serum fibrosis indices. It also had the highest diagnostic performance in estimating Scheuer stage III and Nakanuma fibrosis score 2, both of which represent portal-bridging fibrosis. Patients with an ELF score of ≥10.0 had shorter survival and presented more frequently clinical complications than those with an ELF score of <10.0. ELF score determines the severity of liver fibrosis and predicts the occurrence of complications and survival in patients with PBC.